Reciprocal Peer Coaching an Instrumental Case Study of the Journey of a Three Year Doctoral Cohort - Bernadowski, Carianne (Advances in Social Sciences Research Journal, 2020)
Reciprocal Peer coaching is a viable pedagogical strategy to use with doctoral students in order to encourage engagement, retention, collaboration, and engagement in a cohort model. This study explored a peer coaching model that randomly paired students in a three-year cohort doctoral program. Results indicated that doctoral candidates found that peer coaching and peer collaboration was beneficial both academically and personally. Moreover, candidates continued their relationship with their peers from year one to year three. Three themes emerged which included random assignment, building relationships through dialogue, and obstacles to success.